Law and the contradictions of the disability rights movement - Bagenstos, Samuel R. (Yale University Press, 2009)
The passage of the Americans with Disabilities Act in 1990 was hailed as revolutionary legislation, but in the ensuing years restrictive Supreme Court decisions have prompted accusations that the Court has betrayed the disability rights movement. Here, the author examines the history of the movement.